Sensing And Controlling The Home Appliances Using Arduino And IoT - J. Aruna santhi, CH. Lakshmi kumari (International Journal of Advanced Science and Technology, 2020)
Home automation or smart home industry have seen dramatic growth in past years and will continue to in future as per the market requirements and it benefits. With the advancement of technology and more dependency of people on smart phone is increasing demands of easy and quick way of solving daily life task, it has become very important to have a technology which can control over the domestic and industrial applications using IOT.  IOT has created the revolution all over the world and in an extremely interesting way. it has become integral part of life.  In our paper we focus on Arduino fundamentals and some sensors to make the way we control our homes appliances. Home automation and home security technique are concentrated as a goal of this paper. The sensors will be interface with Arduino. Updates of home appliances will get uploaded to a cloud platform through wireless module. Here the home automation system and mobile are connected over same wireless network. Sensors will have the option to empower or debilitate the sensors which will be in charge of the client. The flex sensor will rely on the motions of our fingers to control the apparatuses.. The magnetic sensor will enhance door breaking security. Every one of this information can be seen by client on the cloud stage like THINKSPEAK. This paper will fill in for instance of how IOT applications can make our life simpler.